2011
DOI: 10.1007/s00776-011-0115-6
|View full text |Cite
|
Sign up to set email alerts
|

Preserving the C7 spinous process in laminectomy combined with lateral mass screw to prevent axial symptom

Abstract: BackgroundPreserving the C7 spinous process during cervical laminoplasty has been reported to prevent axial symptom. Some patients underwent laminectomy and fixation developed the symptom. The objective of this article was to investigate whether axial symptom can be reduced by preserving the C7 spinous process during cervical laminectomy and fixation with lateral mass screw.MethodsBetween 2005 and 2008, data of 53 patients who underwent laminectomy and lateral mass-screw fixation for multilevel cervical myelop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…Takeuchi et al [30] and Zhang et al [31] demonstrated that the C7 spinous process might play an important role in preventing axial symptoms, and axial symptom severity might be affected by musculature atrophy. Axial symptoms might also be caused by other problems, such as nuchal muscle intraoperative injury, destruction of facet joints, intraoperative nerve root damage and hinge side nonunion.…”
Section: Discussionmentioning
confidence: 99%
“…Takeuchi et al [30] and Zhang et al [31] demonstrated that the C7 spinous process might play an important role in preventing axial symptoms, and axial symptom severity might be affected by musculature atrophy. Axial symptoms might also be caused by other problems, such as nuchal muscle intraoperative injury, destruction of facet joints, intraoperative nerve root damage and hinge side nonunion.…”
Section: Discussionmentioning
confidence: 99%
“…Laminectomy resulted in the enhancement of the JOA score post operation and above 50% of the recovery rate [28][29][30][31]. These studies indicate that this technique provides adequate decompression to the spinal cord.…”
Section: Clinical Outcomementioning
confidence: 65%
“…A study by Zhang et al [29] reported that preserving the C7 spinous process during laminectomy reduces the risk of postoperative axial neck pain. Moreover, the authors [29] found that the axial neck pain is correlated with musculature atrophy after the procedure. Another complication of laminectomy is C5 palsy [30,31].…”
Section: Surgical Outcomementioning
confidence: 99%
“…To prevent axial pain, the operation level of CL has been limited from C3 to C6 and the C7 lamina has been cut in a dome-shape when involved 106,107) . However, even after this countermeasure, some patients continue to have complaints.…”
Section: Axial Pain After CLmentioning
confidence: 99%